Past-Positive time perspective predicts academic achievement via motivation, and procrastination might not be as bad as it seems - Fernández Da Lama, Rocío Giselle (2022)
Fil: Fernández Da Lama, Rocío Giselle. Pontificia Universidad Católica Argentina; Argentina